Sensoriamento proximal para estimativa da acidez potencial do solo - Nicolodi, Nidgia Maria (2023)
Soil acidity reduces crop productivity and the application of lime is capable of inhibiting its effects. However, the necessary limestone must be quantified taking into account the heterogeneity of the soil, to reduce costs and increase liming efficiency. As a result, precision agriculture tools, such as the use of sensors, can optimize and improve data collection, providing an alternative to the standard method, which is costly, time-consuming and destructive. Therefore, the objective of this work was to validate the Sb sensor for in situ pH measurements and propose a method for estimating potential soil acidity using the pH sensor and the TSM solution instantly. To achieve this, the pH sensor was initially evaluated on a laboratory bench and subsequently in the field. For laboratory measurements, processed and fresh samples were used. In the field, the data generated by the sensor were compared to the traditional method adopted in precision agriculture to generate pH maps. After validating the sensor to determine active soil acidity, evaluations began to estimate potential acidity. To this end, tests were carried out in the laboratory using Santa Maria buffer solution (TSM), added in different ways to processed soil, with evaluations of the variables concentration and time. To determine active acidity, it was verified that it is essential to process data and humidity in the sample during the measurement. In the evaluations to estimate the potential acidity, promising results were obtained, as it was observed that just 15s of contact between the sensor and the sample are enough to obtain data in agreement with the standard method, dispensing with rest and agitation. It was verified that the addition of the TSM solution 3:1 (distilled water:TSM solution ratio) measured at pH 7.5, ensured that the soil exerted its buffering power, as the method presented an error of less than 5% compared to the values of the SMP index. of the same samples. Thus, the studies in this work made it possible to validate the Sb sensor for generating accurate pH maps and the pH sensor was able to estimate the potential acidity of the soil, together with the TSM solution, at bench level.